Investigation into the Efficacy of Val-SN-38, a Valine-Ester Prodrug of the Anti-Cancer Agent SN-38 - Kwak, Eun-Young; Choi, Min-Koo; Yang, Su-Geun; Shim, Chang-Koo; Shim, Won-Sik (Biomolecules & therapeutics, 2012)
We recently reported that Val-SN-38, a novel valine ester prodrug of SN-38, had greatly improved the intracellular accumulation of SN-38 in MCF-7 cell line, probably through enhanced uptake via amino acid transporters. In the present study, the efficacy of Val-SN-38 was further investigated both in vitro and in vivo. It was found that the in vitro cytotoxic effect of Val-SN-38 was similar to that of SN-38. Moreover, Val-SN-38 exhibited an equal potency to that of SN-38 in survival experiments in vivo. Because these results seemed to be contrary to the previous finding, further investigation was performed to find out the underlying cause of the contradiction. As only the lactone form is known to have cytotoxic activity, the proportion of lactone in Val-SN-38 and SN-38 was determined, but no differences were found. However, it turned out that Val-SN-38 had poor stability compared with SN-38, which resulted in a decrease in beneficial efficacy for Val-SN-38. Overall, the present study showed that a valine-added prodrug approach could be advantageous provided that the stability of the compound can be ensured. We believe this is a noteworthy study that unravels the discrepancy between intracellular accumulation and efficacy of valine-added prodrug.